Validation of a railway inline seating model for occupants injury biomechanics - Carvalho, Marta (2018)
This paper presents the validation of a finite element model in LS-DYNA of the interior inline seating layout simulating a frontal rail impact event for which the experimental test results provide the reference for the injury biomechanics of the occupants. The representative layout consists in two rows of seats and its supporting structures modelled with nonlinear finite elements and the crash acceleration pulse that represents the impact of the railway vehicle structure is imposed in the floor of the coach. For the appropriate identification of the injury mechanisms to the occupant associated to the frontal crash analysis is used the Hybrid III 50th percentile Anthropomorphic Testing Device, being the interaction between the occupant model and the structure characterised via penalty contact force models. The validity of the numerical model is discussed to ensure the representativeness of the analysis procedure and to identify the most relevant injury indices of the occupants. In particular, the head injury criterion is the most critical injury index for the inline seating layout, with a relative deviation of 6.2% of the simulation result with respect to the experimental test.